Exploring a necessity of technical skills for an informal roadside metalwork fabrication apprenticeship practice - Awang, Halizah; Kankia, Jamilu Danyaro; Roddin, Rohayu; Daud, Zawawi; Abd Rahman, Azmanirah; Yasak, Zurina (Penerbit UTHM, 2021)
There was range of disadvantages in the informal roadside metalwork fabrication apprenticeship practice in north western Nigeria that includes the lack of appropriate technical skills to better serve the society. The purpose of this research was to identify those technical skills needed for the informal roadside metalwork fabrication apprenticeship practice in Nigeria. To this effect an investigation was carried out through a survey research, using questionnaire instrument and interview as entailed by methodological triangulation. The survey research was conducted using 140 population of master craft persons from sampled workshops in seven states of North West geopolitical zone of Nigeria, using structured questionnaire instrument. Interview of 10 participants was made, who were randomly selected from, industry-based trainers, lecturers and instructors within the seven states in north western Nigeria. The interviews were conducted to ensure a balance result. Open coding was made, followed by Axial coding. Selective coding was lastly made and the results were interpreted as it complemented the descriptive results which entailed the methodological triangulation method. To validate the results obtained from methodological triangulation, eleven Delphi panel of experts were involved. Binary analysis and Kendall’s coefficient of concordance (Kendall’s Wa) were used to measure and determine the consensus of the experts on the technical skills items. Positive results were obtained because, the level of consensus between the participants was 0.621.The results also indicated an inter-judge reliability. Suggestions were made for the improvement of the sector, as the appropriate and valid technical skills needed were outlined.